Effects of Volume Fraction and Chemical Reaction on Inclined MHD Two-Phase Biorheological Flow in a Porous Tumor Region: Heat and Mass Transfer with Soret Effect (European Journal of Pure and Applied Mathematics, 2025)
Blood transport has many crucial answers and unanswered questions responsible for the formation of metastasis, growth, and effective treatments. In any therapy (radiotherapy, chemotherapy, or immunotherapy), blood carries the required agents, such as oxygen or pharmacological agents. Blood viscosity and concentration are important factors to study. Two-phase biorheology of the blood is considered with chemical reaction and volume fraction. Heat and mass transport are proposed to be studied with the Soret application. The angle of inclination of the applied magnetic field is 0 to 90 degrees. The concentrated agents (drugs) carried by the blood create chemical reactions in the surrounding medium. Thus, the mathematical model is governed by partial differential equations (PDEs) for fluid transport, heat transport, and mass transport.  These equations are solved using the mathematical function PDEPE in the software MATLAB. These transport interactions in tumor regions are obtained for fluid velocity, suspension velocity, thermal profiles, and concentration profiles for parameters like Soret number (Sr), volume fraction ( ), magnetic intensity (M), Chemical reaction parameter ( ), thermal radiation parameter (Rd), etc. These results are validated through graphs and tables obtained. Soret effects vary, which reduces transport velocity, which will support drug delivery systems. Thermal parameters on blood flow, heat stress, and concentration that help in tumor treatments are described using numerical outputs and depicted through graphs.